Implementation of Collaborative Governance in Flood Management in the Greater Bandung Area - Rulinawaty Rulinawaty; Lukman Samboteng; Sofjan Aripin; M Rachmat Kasmad; Mutmainnah Basit (Universitas Sultan Ageng Tirtayasa, 2022)
Indonesia is a country that is prone to natural disasters, especially floods. This disaster usually hits Indonesia during the rainy season. This hurts human life, the economy and the environment. This paper aims to examine collaborative governance implementation in flood management that occurs in the Greater Bandung area. The research method used is a literature study with qualitative methods. The research location is a flood-prone area, namely 4 (four) districts/cities around the Greater Bandung metropolitan area in West Java Province, Indonesia. All of them have a high flood hazard index. In conclusion, sustainable flood management requires the involvement and participation of various stakeholders from the community simultaneously. Flood management in collaborative governance must be carried out with a systematic approach and synergy from multiple disaster management efforts. Therefore, strengthening a sense of crisis, commitment, shared roles and responsibilities, and continuity of cooperation/collaboration in governance networks is needed to maintain effective flood management.